Psalm 22 : to pray like Jesus prayed - Mare, L. P. (Old Testament Essays, 2004)
Psalm 22 is one of the so-called messianic psalms. According to this viewpoint, the psalm should be interpreted as a direct prophecy of the suffering of Jesus. However, such a reading of the psalm completely ignores the historical situation of the psalm and also reduces the Old Testament to promise with the fulfilment only taking place in the New Testament. Instead of interpreting the psalm as a prophecy and Jesus' use thereof as the fulfilment, it should rather be understood as an actualisation of the psalm in new circumstances. Jesus' utilization of Psalm 22 paves the way for all believers to use it in times of suffering. Because of a personal relationship with God, all believers have the right to pray like Jesus prayed.
free